Incipient Musings on Theory and Formation of Modern Korean Digraphia - Strnad, William (Investigationes Linguisticae, 2019)
This article explores modern Korean digraphia, its chracteristics, duality and formation. The author posits that the essential axis of argumentation of the Korean digraphic debate related to the applications of Chinese characters and Korean phonetic script was formed by the early part of the twentieth century, and would be recapitulated in the two Koreas against the backdrop of post-colonial metanarration and Cold War politics. The author asserts that the functional and synchronic nature of modern Korean digraphia was formed under the influence of the Lyotardian modernity emancipation and speculative (science) metanarratives, as well as the discourse of modern Korean nationalism, which synchronically formed in the Korean assertion of national identity and idependence, during Koreaʼs struggle against imperialism.